Peran Acara Pekan Kebudayaan Nasional terhadap Persepsi Mahasiswa tentang Kualitas Pendidikan Bahasa dan Sastra Indonesia - Melsa Nurpuzianah; Hindun Hindun (LPPM Politeknik Pratama, 2024)
This research explores the role of the 2023 National Cultural Week (Pekan Kebudayaan Nasional - PKN) in shaping the perceptions of students majoring in Indonesian Language and Literature Education at UIN Syarif Hidayatullah Jakarta regarding the quality of literary education. Utilizing a qualitative approach, the study investigates student participation, highlighting a high interest in the